Acceptability of ENG‐releasing subdermal implants among postpartum Brazilian young women during the COVID‐19 pandemic. Issue 1 (29th April 2021) - Barbieri, Mariane Massaini; Herculano, Thuany Bento; Dantas Silva, Amanda; Bahamondes, Luis; Juliato, Cassia Raquel Teatin; Surita, Fernanda Garanhani
Abstract: Objective: To evaluate etonogestrel (ENG)‐implant acceptance during the immediate postnatal period among adolescents and young women during the COVID‐19 pandemic, and to compare variables according to choice and discuss possible implications of this measure during the pandemic period. Methods: A cross‐sectional study was designed. All women aged up to 24 years, who delivered between April 25, 2020, and June 24, 2020, at Women's Hospital, University of Campinas, São Paulo, Brazil were considered. The ENG‐implant or other contraceptive methods were offered prior to hospital discharge. The participants were split into two groups: (1) those who chose the ENG‐implant and (2) those that refused the implant. Descriptive, bivariate, and multivariate analyses were performed. Results: 151 women were included, with 76.2% selecting the ENG‐implant. The average age was 19.5 years; 73.2% of pregnancies were unplanned, 32.5% already had a previous pregnancy, 74% were single, and 75.5% were not in full time education. Further, 70.5% had previously used contraceptives, with 89.1% unsatisfied with their previous method that opted for the ENG‐implant ( P  = 0.07). Conclusion: Offering the ENG‐implant to youths during the immediate postnatal period is evidence‐based care, and contraceptive provision is an essential health promotion tool, even during a pandemic. Thinking quickly about public policies in times of crisis is important to guarantee sexual and reproductive rights. Synopsis: During the COVID‐19 pandemic, the offer of ENG‐implants in the immediate postnatal period for young women is an essential health activity and broad acceptance must be considered and expanded.